Impact of information and communication technologies on corporate energy intensity: evidence from cross-country micro data - Wen, Huwei; Jiang, Meng; Zheng, Shufang (Journal of environmental planning and management, 2024)
Using a sample of manufacturing enterprises from the World Bank Survey during the period from 2006 to 2020, this study explores the impact of information and communication technologies (ICT) on corporate energy intensity and its mechanisms. Empirical results show that ICT adoption significantly improves the energy intensity of manufacturing enterprises in emerging and developing countries; a change in the standard deviation of ICT adoption can contribute 22.58% of the difference in corporate energy intensity. On the one hand, ICT adoption intensifies market competition and reduces product price markups, leading manufacturing enterprises to reduce investment in energy conservation. On the other hand, ICT adoption is complementary to energy and can promote energy input to replace traditional factors such as labor and capital, thereby increasing corporate energy intensity. The market competition effect and factor substitution effect account for 14.96% and 73.71% of the total effect. This study also confirms the Solow Productivity Paradox in ICT adoption, leading to the failure of the productivity mechanism for ICT to reduce energy intensity.